Effects of human C-reactive protein on pathogenesis of features of the metabolic syndrome - Pravenec, Michal; Kajiya, Takashi; Zídek, Václav; Landa, Vladimír; Mlejnek, Petr; Simáková, Miroslava; Silhavý, Jan; Malínská, Hana; Oliyarnyk, Olena; Kazdová, Ludmila; Fan, Jianglin; Wang, Jiaming; et al. (Hypertension (Dallas, Tex., 2011)
Major controversy exists as to whether increased C-reactive protein (CRP) contributes to individual components of the metabolic syndrome or is just a secondary response to inflammatory disease processes. We measured blood pressure and metabolic phenotypes in spontaneously hypertensive rats (SHRs) in which we transgenically expressed human CRP in the liver under control of the apolipoprotein E promoter. In transgenic SHRs, serum levels of human CRP approximated the endogenous levels of CRP normally found in the rat. Systolic and diastolic blood pressures measured by telemetry were 10 to 15 mm Hg greater in transgenic SHRs expressing human CRP than in SHR controls (P<0.01). During oral glucose tolerance testing, transgenic SHRs exhibited hyperinsulinemia compared with controls (insulin area under the curve: 36±7 versus 8±2 nmol/L per 2 hours, respectively; P<0.05). Transgenic SHRs also exhibited resistance to insulin stimulated glycogenesis in skeletal muscle (174±18 versus 278±32 nmol of glucose per gram per 2 hours; P<0.05), hypertriglyceridemia (0.84±0.05 versus 0.64±0.03 mmol/L; P<0.05), reduced serum adiponectin (2.4±0.3 versus 4.3±0.6 mmol/L; P<0.05), and microalbuminuria (200±35 versus 26±5 mg of albumin per gram of creatinine, respectively; P<0.001). Transgenic SHRs had evidence of inflammation and oxidative tissue damage with increased serum levels of interleukin 6 (36.4±5.2 versus 18±1.7 pg/mL; P<0.005) and increased hepatic and renal thiobarbituric acid reactive substances (1.2±0.09 versus 0.8±0.07 and 1.5±0.1 versus 1.1±0.05 nmol/L per milligram of protein, respectively; P<0.01), suggesting that oxidative stress may be mediating adverse effects of increased human CRP. These findings are consistent with the hypothesis that increased CRP is more than just a marker of inflammation and can directly promote multiple features of the metabolic syndrome.
Keywords: Insulin; oxidační stres; adiponektin; Analysis of Variance; potkani transgenní; inzulin; krevní glukóza; potkani inbrední SHR; C-reaktivní protein; metabolický syndrom; Telemetry; Rats, Transgenic; Metabolic Syndrome; krysa rodu Rattus; Animals; lidé; krevní tlak; analýza rozptylu; telemetrie; Humans; zvířata; Rats; Blood Pressure; Adiponectin; Rats, Inbred SHR; Glucose Tolerance Test; C-Reactive Protein; Oxidative Stress; Blood Glucose; glukózový toleranční test